IMPLEMENTASI TERAPI DIAPHRAGMATIC BREATHING EXERCISE TERHADAP PERUBAHAN RESPIRATORY RATE PADA PASIEN TB PARU DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Siregar, Endang Kristina; Susyanti, Deni; Gea, Handerman Vitu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Pumonary tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, which primarily attacks the human lungs. The main complaints in pulmonary TB patients are shortness of breath and cough caused by the bacterial infection entering the lungs. One nursing intervention that can be provided to pulmonary TB patients to address ineffective breathing patterns is diaphragmatic breathing exercise. This study used a descriptive method with a case study design. The case study applied the nursing care process with implementation in two patients with pulmonary TB at TK II Putri Hijau Hospital in Medan. After implementing diaphragmatic breathing exercises for three days, the problem of ineffective breathing patterns in both patients was resolved. The results of this study indicate that diaphragmatic breathing exercise therapy can effectively address ineffective breathing patterns in patients with pulmonary TB.